Multifaceted antimicrobial mechanisms of NCR147-derived peptides from Medicago truncatula - Tiricz, Hilda; Lima, Rui M.; Pfeiffer, Ilona; Igaz, Nóra; Domonkos, Ildikó; Jenei, Sándor; Howan, Dian H. O.; Pál, Alexandra; Tímár, Edit; Hunyadi-Gulyás, Éva; Tóth, Gábor K.; Bozsó, Zoltán; et al. (Frontiers in Microbiology, 2026)
IntroductionAntimicrobial peptides (AMPs), key components of innate immunity, offer broad-spectrum activity against diverse pathogens. In Medicago truncatula, over 700 nodule-specific cysteine-rich (NCR) peptides with highly diverse sequences and physicochemical properties are produced in the symbiotic cells of root nodules, where cationic members block bacterial cell division and display potent antimicrobial activity in vitro. In contrast, anionic NCRs typically lack antimicrobial effects, and NCR147—a neutral peptide—is the only known non-cationic NCR that shows weak bactericidal activity. This unique property prompted us to identify the antimicrobial region of NCR147 and enhance its activity through targeted sequence modifications.Materials and methodsIn this study, 13 truncated and substituted derivatives of NCR147 were chemically synthesized to identify peptide regions responsible for antimicrobial activity. Antimicrobial efficacy was evaluated against 18 pathogens by determining minimum bactericidal and minimum fungicidal concentrations. Inhibition and eradication of bacterial biofilms were assessed to determine peptide effects. Cytotoxicity was measured using hemolysis assays and multiple viability assays in human cell cultures. Peptide interactions with membrane lipids, effects on membrane permeability, and modulation of bacterial efflux pumps were analyzed using established biochemical and biophysical assays. Bacterial proteins interacting with selected peptides were identified by affinity chromatography followed by LC–MS/MS.ResultsThe NCR147 derivatives displayed varying degrees of antimicrobial potency and spectrum. Analysis of the physicochemical properties and predicted 3D structures of 13 NCR peptide variants revealed that the antimicrobial region resides in the C-terminal portion of these intrinsically disordered peptides, where the WAW hydrophobic patch together with the positively charged amino acids contribute to antimicrobial activity, most likely through interactions with microbial membranes. The most active peptides provoked alteration of bacterial membranes, inhibited efflux pumps, and interfered with essential intracellular targets. Moreover, these peptides exhibited potent antibiofilm effects, including the ability to both prevent and degrade Acinetobacter baumannii biofilms. Incorporation of 5-fluoro-L-tryptophan enhanced both antimicrobial breadth and antifungal activity. Importantly, this fluorinated peptide was non-cytotoxic to human cells.DiscussionThese findings reveal that NCR147-derived peptides function via a multihit mechanism and highlight the therapeutic promise of plant-derived AMPs as next-generation antimicrobials with reduced risk of resistance development.